2018
DOI: 10.1016/j.biopsycho.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural inhibition responses to food cues after Roux-en-Y Gastric Bypass

Abstract: Neural changes indicate improved response inhibition towards high-energy food cues, altered influence of metabolic control during response inhibition towards low-energy food cues and a more positive attitude to both high-energy and low-energy food after RYGB. Alterations in neural circuits involved in inhibitory control, satiety signalling and reward processing may contribute to effective weight-loss after RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…PHIPP is also implicated in food craving, the physiologic state of hunger, when motivationally relevant food objects are shown [14], and when tasting a liquid meal. Several neuroimaging studies showed increased PHIPP activation to high-energy visual food cues and decreased PHIPP activation after weight loss surgery [31]. Our previous study also showed that WM densities were lower in PHIPP in obese relative to healthy weight individuals.…”
Section: Alterations In Regions Associated With Memorysupporting
confidence: 49%
“…PHIPP is also implicated in food craving, the physiologic state of hunger, when motivationally relevant food objects are shown [14], and when tasting a liquid meal. Several neuroimaging studies showed increased PHIPP activation to high-energy visual food cues and decreased PHIPP activation after weight loss surgery [31]. Our previous study also showed that WM densities were lower in PHIPP in obese relative to healthy weight individuals.…”
Section: Alterations In Regions Associated With Memorysupporting
confidence: 49%
“…Similarly to the effects of GLP-1R agonism described above, RYGB surgery reduces insula and PFC BOLD signals in response to visual and auditory food cues in fasted obese women [45]. RYGB surgery also increases precuneus BOLD response to low fat/sugar food cues while decreasing response to high fat/sugar food cues [46]. Finally, weight loss and decreased appetite for sweet and fat foods after RYGB surgery coincides with reduced resting-state functional connectivity between the insula and the anterior cingulate as well as improved sensitivity of the default mode network to GLP-1R blockade [47].…”
Section: Human Studiesmentioning
confidence: 83%
“…Using fMRI, obese subjects present attenuated hypothalamic signals in response to glucose [8,10], cold [11], overfeeding [24], and food image cues [25]. Available data also suggest that such obesity-associated abnormalities in hypothalamic responses can be ameliorated following body mass reduction obtained as a result of a RYGB [10,26].…”
Section: Discussionmentioning
confidence: 99%